Epoxy primer and preparation method thereof
By compounding aliphatic flexible epoxy resin and bisphenol A-type epoxy resin in the epoxy primer, the problems of poor adhesion and insufficient impact resistance of the existing epoxy zinc-rich paint on the substrate are solved. Better paint film adhesion and impact resistance.
Patent Information
- Application Number
- CN202411689094.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing epoxy zinc-rich paint has poor adhesion on substrates such as stainless steel, aluminum alloy, galvanized steel, etc., and the paint film is prone to fall off, resulting in poor application effect of energy storage boxes.
Provides a type of epoxy primer. It is reproduced through the alipan flexible epoxy resin and bisphenol -A -type epoxy resin to increase the adhesion and impact resistance of the epoxy resin after curing, and improve the cooling and cold shock performance of the paint film.
It significantly improves the adhesion, impact resistance and cooling and cold shock of the paint film, avoiding cracking and stripping due to tremor, and extending the service life of the paint film and substrate.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating compositions, and in particular relates to an epoxy primer and a preparation method thereof. Background Art
[0002] The regions and environments where energy storage boxes are used are complex, and there are high requirements for the corrosion resistance and impact resistance of the surface paint film. In addition, during the use of the energy storage box, due to factors such as structural design, materials, internal failures, installation foundation, mechanical imbalance, and external environment, different degrees of vibration may occur, causing the surface paint film to peel, crack, or even peel off. The complex use environment will also cause the stress on the box to change frequently, causing the paint film coating to age and fail due to fatigue. All of these will accelerate the corrosion of the box base material.
[0003] At present, epoxy zinc-rich paint is commonly used as the primer of energy storage boxes. The material cost is high and the surface treatment of the substrate is strict. At the same time, the adhesion of epoxy zinc-rich paint on substrates such as stainless steel, aluminum alloy, and galvanized steel is poor, and the paint film is easy to fall off, so the application effect on energy storage boxes is not good.
[0004] In summary, the prior art obviously has inconveniences and defects in practical use, so it is necessary to improve it. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention mainly provides an epoxy primer to solve the technical problems that the paint film of the existing primer on the substrate is brittle and has low adhesion to the substrate.
[0006] In order to solve the above problems, the present invention provides an epoxy primer, comprising component A and component B, wherein the mass ratio of component A to component B is 5-7:1;
[0007] Calculated by weight, the component A includes: 15-35 parts of bisphenol A epoxy resin, 1-5 parts of aliphatic flexible epoxy resin, 0.5-5 parts of rheology control additive, 5-14 parts of cosolvent, 0.4-1 parts of wetting dispersant, 0.1-0.6 parts of defoamer, 10-20 parts of pigment, 10-30 parts of wear-resistant filler, 5-15 parts of anticorrosive filler, and 0.4-1 parts of leveling agent;
[0008] Calculated by weight, the B component includes: 40-70 parts of polyamide curing agent, 1-5 parts of epoxy drier, and 15-30 parts of cosolvent.
[0009] According to the epoxy primer of the present invention, the epoxy equivalent of the bisphenol A epoxy resin is 450-500 g / mol; the aliphatic flexible epoxy resin is a polyglycol diglycidyl ether resin, with an epoxy equivalent of 310-330 g / mol, a solid content of ≥99%, and a viscosity of 50-80 mPa·s.
[0010] According to the epoxy primer of the present invention, the wear-resistant filler is: a compound of precipitated barium sulfate and polyurethane microspheres; the weight parts of the precipitated barium sulfate and the polyurethane microspheres are both: 5-25 parts, and the sum of the weight parts of the two is 10-30 parts.
[0011] According to the epoxy primer of the present invention, the solid content of the polyurethane microspheres is ≥99%, the oil absorption is 70-120%, and the particle size is <50µm.
[0012] According to the epoxy primer of the present invention, the polyurethane microspheres are Acure D820.
[0013] According to the epoxy primer of the present invention, the anticorrosive filler is a compound of aluminum tripolyphosphate and calcium-based bentonite, the weight parts of the two are both: 2-10 parts, and the sum of the weight parts of the two is 5-15 parts.
[0014] According to the epoxy primer of the present invention, the polyamide curing agent is 200 low molecular weight polyamide, the solid content is ≥99%, and the amine value is: 230-260 mg KOH / g.
[0015] According to the epoxy primer of the present invention, the epoxy drier is: 2,4,6-tris(dimethylaminomethyl)phenol.
[0016] According to the epoxy primer of the present invention, the defoamer is: a polymer defoamer that does not contain silicone;
[0017] The wetting and dispersing agent is: a modified polyurethane polymer;
[0018] The rheology control additive is: a polyamide wax expansion particle dispersion with 20% effective ingredients;
[0019] The leveling agent is: an acrylic polymer surface control agent having 50% non-volatile matter;
[0020] The pigment is: titanium dioxide, phthalocyanine blue, carbon black, iron oxide red or iron oxide yellow;
[0021] The co-solvent is: xylene, methyl ethyl ketone, n-butanol or isopropanol.
[0022] A method for preparing the epoxy primer comprises:
[0023] The preparation of component A comprises the following steps:
[0024] S1: adding the bisphenol A epoxy resin, aliphatic flexible epoxy resin and rheology control agent into a mixing tank according to predetermined weight portions; stirring for 10-30 minutes, and controlling the fineness to be ≤20 µm;
[0025] The stirring speed is: 2000~3000r / min, and the temperature in the batching tank is: 40-60℃;
[0026] S2: adding a cosolvent, a wetting and dispersing agent, a defoaming agent, a pigment, a wear-resistant filler, an anticorrosive filler, and a leveling agent according to predetermined weight portions, and stirring to obtain a mixed solution;
[0027] Stirring speed: 1000~1500 r / min;
[0028] S3: transferring the mixed solution to a grinding tank and grinding it to a predetermined fineness; the temperature in the grinding tank is: 20-40°C;
[0029] S4: reducing the stirring speed to 1000 r / min, adding a co-solvent, stirring evenly, and filtering through a 100-mesh filter to obtain the A component;
[0030] Preparation of the B component:
[0031] Adding a cosolvent, a polyamide curing agent, and an epoxy drier into a batching tank according to predetermined weight portions; stirring evenly, and filtering through a 120-mesh filter to obtain the B component;
[0032] The stirring speed is: 500~1500r / min, and the stirring time is: 40-60min.
[0033] In summary, the epoxy primer of the present invention increases the adhesion and impact resistance of the epoxy resin after curing by compounding aliphatic flexible epoxy resin with bisphenol A epoxy resin, and improves the cold and hot shock resistance of the paint film. It avoids the problems of cracking and peeling caused by vibration when the primer is applied to the energy storage box. The present invention also provides a preparation method of the epoxy primer. DETAILED DESCRIPTION
[0034] The present invention provides an epoxy primer, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is 5 to 7:1;
[0035] Calculated by weight, the component A includes: 15-35 parts of bisphenol A epoxy resin, 1-5 parts of aliphatic flexible epoxy resin, 0.5-5 parts of rheology control additive, 5-14 parts of cosolvent, 0.4-1 parts of wetting dispersant, 0.1-0.6 parts of defoamer, 10-20 parts of pigment, 10-30 parts of wear-resistant filler, 5-15 parts of anticorrosive filler, and 0.4-1 parts of leveling agent;
[0036] Calculated by weight, the B component includes: 40-70 parts of polyamide curing agent, 1-5 parts of epoxy drier, and 15-30 parts of cosolvent;
[0037] The polyamide curing agent of the present invention contains active hydrogen atoms, which can undergo cross-linking reaction with the epoxy groups of the bisphenol A epoxy resin, thereby increasing the cross-linking density of the paint film, and further increasing the heat resistance and corrosion resistance of the paint film.
[0038] The main chain of the aliphatic flexible epoxy resin of the present invention has a fatty chain. The structure of the fatty chain is relatively simple, and the carbon atoms in the fatty chain are connected by single bonds, so it can rotate freely and has less steric hindrance. The present invention adopts a method of compounding aliphatic flexible epoxy resin and bisphenol A epoxy resin, and introduces it into the epoxy resin main chain, which can significantly reduce the steric hindrance in the molecular chain, thereby changing the conformation of the molecular chain. It can also affect other parts connected to the fatty chain, so that the rotational freedom of the entire molecular chain is increased. Based on the changes in the microstructure, the primer of the present invention is macroscopically manifested as flexibility, adhesion and impact resistance are effectively improved. Thereby reducing the brittleness of the paint film and avoiding problems such as cracking and peeling.
[0039] Existing primer formulas usually require additional toughening agents to improve flexibility. However, the additional addition of toughening agents not only increases costs, but also affects the drying speed and salt water resistance of the primer. The aliphatic flexible epoxy resin of the present invention can also improve the flexibility of the primer, reduce the brittle cracking of the paint film, and avoid the problems caused by the additional addition of toughening agents.
[0040] The present invention increases the adhesion and impact resistance of the cured epoxy resin by compounding the aliphatic flexible epoxy resin with the bisphenol A epoxy resin, and improves the cold and hot shock resistance of the paint film, thereby avoiding the problems of cracking and peeling caused by vibration when the primer is applied to the energy storage box.
[0041] As a preferred embodiment, the epoxy equivalent of the bisphenol A epoxy resin of the present invention is 450-500 g / mol; the aliphatic flexible epoxy resin is a polyglycol diglycidyl ether resin; the epoxy equivalent is 310-330 g / mol, the solid content is ≥99%, and the viscosity is 50-80 mPa·s.
[0042] The aliphatic flexible epoxy resin of the present invention is used as one of the film-forming substances of the epoxy primer, and its epoxy equivalent, solid content and viscosity will affect the performance of the epoxy primer.
[0043] The epoxy equivalent of the aliphatic flexible epoxy resin of the present invention is set to: 310-330 g / mol; the use of the aliphatic flexible epoxy resin within the epoxy equivalent range can reduce the hardness and brittleness of the primer film and improve the impact resistance, thermal shock resistance and salt spray resistance of the film.
[0044] The solid content of the aliphatic flexible epoxy resin of the present invention is ≥99%; the use of a higher solid content can increase the drying speed of the primer, increase the thickness of the paint film, and further improve the weather resistance and aging resistance of the paint film;
[0045] The viscosity of the aliphatic flexible epoxy resin of the present invention is 50-80 mPa·s. The aliphatic flexible epoxy resin within the viscosity range can increase the compatibility with the aliphatic flexible epoxy resin bisphenol A type epoxy resin. The adhesion and covering effect of the paint film are improved. The paint film has higher adhesion, flexibility and corrosion resistance, and the service life of the paint film is extended. At the same time, the epoxy primer can be easily applied and leveled during the construction process, and the generation of bubbles and pinholes can be reduced.
[0046] Optionally, the bisphenol A epoxy resin of the present invention is: NPSN-901X75, NPSN-901S75, NPSN-901K80 or NPSN-900X75.
[0047] Optionally, the aliphatic flexible epoxy resin of the present invention is: DER732.
[0048] As a preferred embodiment, the wear-resistant filler of the present invention includes precipitated barium sulfate, which can increase the coating thickness of the epoxy primer and improve the wear resistance of the coating film.
[0049] Since barium sulfate has a relatively high density, it is easy to precipitate in the primer, resulting in uneven distribution of barium sulfate in the paint film, making the hardness of the paint film surface different, resulting in excessive hardness in some parts of the paint film, increased brittleness, etc., which makes it more likely to break or break when impacted.
[0050] Furthermore, the wear-resistant filler also includes polyurethane microspheres; the precipitated barium sulfate and the polyurethane microspheres are compounded, and the weight parts of the two are both 5 to 25 parts, and the sum of the weight parts of the two is 10 to 30 parts.
[0051] By compounding polyurethane microspheres with precipitated barium sulfate, the precipitated barium sulfate particles can be better fixed and the effect of precipitated barium sulfate on the hardness of the paint film can be weakened. When the paint film is impacted by external forces, it can better absorb energy, prevent brittle fracture or reduce crack expansion.
[0052] Preferably, the polyurethane microspheres have a solid content of ≥99%, an oil absorption of 70-120%, and a particle size of <50 µm.
[0053] Polyurethane microspheres with high solid content can increase the paint film thickness of epoxy primer, improve its impact resistance and corrosion resistance; enhance the adhesion between epoxy primer and substrate, making the paint film more firm and less likely to fall off.
[0054] The polyurethane microspheres of the present invention have a set oil absorption of 70-120% and a particle size of less than 50 μm, which is conducive to fixing the precipitated barium sulfate particles, making the two evenly dispersed in the primer and tightly filling the tiny gaps in the paint film. The viscosity and adhesion of the primer can be optimized, and the leveling property of the epoxy primer can be improved, making the surface of the paint film smoother and more uniform.
[0055] Optionally, the polyurethane microspheres are Acure D820.
[0056] The present invention forms a wear-resistant filler by compounding polyurethane microspheres with precipitated barium sulfate. The physical barrier formed by the polyurethane microspheres is combined with the tight filling of the precipitated barium sulfate to construct a multi-layer protective barrier. The adhesion of the paint film is increased, the impact resistance and flexibility of the paint film are improved, and the phenomenon of falling off or peeling off during use is prevented. At the same time, the paint film can effectively prevent corrosive media such as moisture, oxygen, and salt from invading the substrate, thereby enhancing the corrosion resistance of the paint film and extending the service life of the paint film and the substrate.
[0057] Preferably, the polyurethane microspheres of the present invention have active groups; the active groups can react with polyamide curing agents to promote the curing process of epoxy resins, help shorten the curing time, and improve production efficiency.
[0058] As a preferred embodiment, the anti-corrosion filler of the present invention includes aluminum tripolyphosphate; aluminum tripolyphosphate can dissociate in the paint film and release tripolyphosphate ions, which can react with metal ions in the substrate to form a dense passive film, thereby preventing further corrosion reactions and improving anti-corrosion performance.
[0059] Furthermore, the anticorrosive filler of the present invention further comprises calcium-based bentonite, and the weight proportions of the aluminum tripolyphosphate and the calcium-based bentonite are both 2 to 10 parts, and the sum of the weight proportions of the two is 5 to 15 parts.
[0060] Calcium-based bentonite has a porous structure. After compounding with aluminum tripolyphosphate, the porous structure provides a large number of attachment points and reaction spaces for aluminum tripolyphosphate, allowing aluminum tripolyphosphate to continuously and stably release tripolyphosphate ions. This avoids the "sudden release" phenomenon caused by the release of a large amount of ions in a short period of time, thereby extending the anti-corrosion period of the paint film.
[0061] Better yet, the anti-corrosion filler aluminum tripolyphosphate and calcium-based bentonite have good compatibility with other ingredients in epoxy primers. The two can be combined to adjust the viscosity of the primer, improve the construction performance of the primer, and make the primer easier to apply and level.
[0062] At the same time, the compounded anti-corrosion filler enhances the adhesion between the paint film and the substrate through synergistic effect, achieving a long-term anti-corrosion effect.
[0063] As a preferred embodiment, the defoamer of the present invention is: a polymer defoamer that does not contain silicone; optionally, the defoamer is: YRXP-02S, AFCONA-2720 or HN505H.
[0064] The wetting and dispersing agent is: modified polyurethane polymer; optionally, the wetting and dispersing agent is: EFKA-4010, HY-4010 or Synde-3010A.
[0065] The rheology control agent is: a polyamide wax expanded particle dispersion with 20% effective ingredients; optionally, the rheology control agent is selected from 6900HV, HY-1020 or 6900-20H.
[0066] The leveling agent is: an acrylic polymer surface control agent with 50% non-volatile matter; optionally, the leveling agent is: DISPARLON L-1980-50.
[0067] The pigment is: titanium dioxide, phthalocyanine blue, carbon black, iron oxide red or iron oxide yellow.
[0068] The co-solvent is: xylene, methyl ethyl ketone, n-butanol or isopropanol.
[0069] As a preferred solution, the polyamide curing agent of the present invention is 200 low molecular weight polyamide, with a solid content of ≥99% and an amine value of 230-260 mg KOH / g.
[0070] The solid content of the polyamide curing agent of the present invention is ≥99%, which can accelerate the speed of the curing reaction, increase the cross-linking density of the cured product, form a tighter network structure, effectively block the penetration and erosion of external media, and improve the chemical resistance of the epoxy primer; so that the epoxy primer can be used in complex environments.
[0071] The amine value of polyamide curing agent will affect the performance of the paint film. If the amine value of the curing agent is too high, it will cause the curing reaction with the epoxy resin to be too fast, causing the paint film to shrink, crack and other defects during the curing process, affecting the flatness and aesthetics of the coating; if the amine value of the curing agent is too low, it will cause the curing reaction with the epoxy resin to be too slow, the degree of cross-linking is too low, and the adhesion and resistance to cold and hot shock of the paint film will be significantly reduced.
[0072] The inventors verified through multiple tests that the amine value of the polyamide curing agent of the present invention is 230-260 mgKOH / g.
[0073] As a preferred embodiment, the epoxy drier of the present invention is 2,4,6-tris(dimethylaminomethyl)phenol, which can react chemically with the polyamide curing agent to reduce the activation energy of the curing reaction. The curing speed is accelerated, the curing time is shortened, and the curing reaction is made more complete and uniform. The generated paint film structure is more compact, and the hardness, wear resistance and corrosion resistance of the paint film are improved.
[0074] Preferably, the 2,4,6-tris(dimethylamino)methylphenol of the present invention is K54.
[0075] The present invention also provides a method for preparing the epoxy primer, comprising:
[0076] The preparation of component A comprises the following steps:
[0077] S1: adding the bisphenol A epoxy resin, aliphatic flexible epoxy resin and rheology control agent into a mixing tank according to predetermined weight portions; stirring for 10-30 minutes, and controlling the fineness to be ≤20 µm;
[0078] The stirring speed is: 2000~3000r / min, and the temperature in the batching tank is: 40-60℃;
[0079] S2: adding a cosolvent, a wetting and dispersing agent, a defoaming agent, a pigment, a wear-resistant filler, an anticorrosive filler, and a leveling agent according to predetermined weight portions, and stirring to obtain a mixed solution;
[0080] Stirring speed: 1000~1500 r / min;
[0081] S3: transferring the mixed solution to a grinding tank and grinding it to a predetermined fineness; the temperature in the grinding tank is: 20-40°C;
[0082] S4: reducing the stirring speed to 1000 r / min, adding a co-solvent, stirring evenly, and filtering through a 100-mesh filter to obtain the A component;
[0083] Preparation of the B component:
[0084] Adding a cosolvent, a polyamide curing agent, and an epoxy drier into a batching tank according to predetermined weight portions; stirring evenly, and filtering through a 120-mesh filter to obtain the B component;
[0085] The stirring speed is: 500~1500r / min, and the stirring time is: 40-60min.
[0086] Better yet, stirring is performed during the adding process to facilitate uniform mixing.
[0087] The component A and the component B are uniformly mixed according to a predetermined weight ratio to obtain the epoxy primer.
[0088] The inventor has set up the formula of multiple embodiments and comparative examples, and prepared epoxy primers using the above-mentioned preparation method. And the prepared epoxy primers have been tested for various performance indicators. The following only lists the epoxy primer formulas of each embodiment and the parameters set by the preparation method, and the same contents are not repeated. Example 1
[0089] Epoxy primer: The mass ratio of component A to component B is 6:1;
[0090] Component A: 20 parts of bisphenol A epoxy resin (NPSN-901X75), 3 parts of aliphatic flexible epoxy resin (DER732), 3 parts of rheology control agent (6900HV), 5 parts of xylene as cosolvent, 0.8 parts of wetting and dispersing agent (EFKA-4010), 0.3 parts of defoaming agent (YRXP-02S), 15 parts of titanium dioxide as pigment, and 0.4 parts of leveling agent;
[0091] The wear-resistant filler is: 25 parts of precipitated barium sulfate, 5 parts of polyurethane microspheres (Acure D820); the anti-corrosion filler is: 5 parts of aluminum tripolyphosphate, 10 parts of calcium-based bentonite;
[0092] Component B: Solvent: 10 parts xylene, 10 parts n-butanol; 40 parts polyamide curing agent, 3 parts epoxy drier (K54);
[0093] Parameters of the preparation method:
[0094] Preparation of component A:
[0095] S1: stirring time: 10 minutes; stirring speed: 2000r / min, temperature in the batching tank: 40℃;
[0096] S2: stirring speed: 1000 r / min;
[0097] S3: The temperature in the grinding jar is: 20°C;
[0098] S4: add 5 parts of n-butanol, stir for 10 minutes and filter;
[0099] Preparation of component B:
[0100] The stirring speed is 500 r / min and the stirring time is 40 min. Example 2
[0101] Epoxy primer: The mass ratio of component A to component B is 7:1;
[0102] Component A: 15 parts of bisphenol A epoxy resin (NPSN-901S75), 1 part of aliphatic flexible epoxy resin (DER732), 0.5 parts of rheology control agent (6900-20H), 5 parts of methyl ethyl ketone as cosolvent, 1 part of wetting and dispersing agent (including 0.5 parts of EFKA-4010 and 0.5 parts of Synde-3010A), 0.1 parts of defoaming agent (including 0.05 parts of AFCONA-2720 and 0.05 parts of HN505H), 10 parts of carbon black as pigment, and 0.8 parts of leveling agent;
[0103] The wear-resistant filler is: 5 parts of precipitated barium sulfate, 5 parts of polyurethane microspheres (Acure D820); the anti-corrosion filler is: 2 parts of aluminum tripolyphosphate, 3 parts of calcium-based bentonite;
[0104] Component B: cosolvent: 15 parts of methyl ethyl ketone; 50 parts of polyamide curing agent, 1 part of epoxy drier (K54);
[0105] Parameters of the preparation method:
[0106] Preparation of component A:
[0107] S1: stirring time: 30 minutes; stirring speed: 3000r / min, temperature in the batching tank: 60℃;
[0108] Optionally, a portion of the co-solvent of the present invention is added in step S1, and the rest is added in subsequent steps; for example, during the stirring process in step S1, 3 parts of the co-solvent, methyl ethyl ketone, is added; and the co-solvent is added in step S4;
[0109] S2: stirring speed: 1500 r / min;
[0110] S3: The temperature in the grinding jar is: 30°C;
[0111] S4: Reduce the speed to 1000r / min, add 2 parts of methyl ethyl ketone, stir for 15 minutes and filter;
[0112] Preparation of component B:
[0113] The stirring speed is: 1500r / min, and the stirring time is: 60min. Example 3
[0114] Epoxy primer: The mass ratio of component A to component B is 5:1;
[0115] Component A: 35 parts of bisphenol A epoxy resin (including 20 parts of NPSN-901K80 and 15 parts of NPSN-900X75), 5 parts of aliphatic flexible epoxy resin (DER732), 5 parts of rheology control agent (HY-1020), 7 parts of xylene as cosolvent, 0.4 parts of wetting and dispersing agent (HY-4010), 0.6 parts of defoaming agent (YRXP-02S), 10 parts of iron oxide red, 10 parts of phthalocyanine blue as pigments, and 1 part of leveling agent;
[0116] The wear-resistant filler is: 5 parts of precipitated barium sulfate, 25 parts of polyurethane microspheres (Acure D820); the anti-corrosion filler is: 10 parts of aluminum tripolyphosphate, 2 parts of calcium-based bentonite;
[0117] Component B: Cosolvent: 30 parts of isopropanol; 70 parts of polyamide curing agent, 5 parts of epoxy drier (K54);
[0118] Parameters of the preparation method:
[0119] Preparation of component A:
[0120] S1: stirring time: 20 minutes; stirring speed: 2000r / min, temperature in the batching tank: 40℃;
[0121] S2: stirring speed: 1500 r / min;
[0122] S3: The temperature in the grinding jar is: 40°C;
[0123] S4: Reduce the speed to 1000r / min, add 7 parts of xylene, stir for 10 minutes and filter;
[0124] Preparation of component B:
[0125] The stirring speed is: 1000r / min, and the stirring time is: 60min.
[0126] The aliphatic flexible epoxy resin in each embodiment is: polyglycol diglycidyl ether resin, the polyamide curing agent is: 200 low molecular weight polyamide; the epoxy drying agent is: 2,4,6-tris(dimethylaminomethyl)phenol.
[0127] The present invention sets four comparative examples corresponding to Example 1; the parameters of the preparation methods of all comparative examples are the same as those of Example 1. Each comparative example replaces a certain component of the epoxy primer of Example 1 in equal amounts, and the other components are the same. Only the replacement components of the epoxy primer of each comparative example and Example 1 are listed below, and the same components are not repeated.
[0128] Comparative Example 1: The aliphatic flexible epoxy resin in Example 1 was replaced with an equal amount of an alicyclic epoxy resin (TaiLuck-2021S); the alicyclic epoxy resin had an epoxy equivalent of 128-145 g / mol and a viscosity of 200-350 mPa·s.
[0129] The NPSN-901X75 in Example 1 was replaced by an equal amount of bisphenol A epoxy resin (DER 331), the epoxy equivalent weight of DER 331 being 182-192 g / mol.
[0130] Comparative Example 2: The polyurethane microspheres (Acure D820) in Example 1 were replaced with an equal amount of precipitated barium sulfate; that is, the wear-resistant filler in Comparative Example 2 was: 30 parts of precipitated barium sulfate.
[0131] Comparative Example 3: The calcium-based bentonite in Example 1 is replaced by an equal amount of aluminum tripolyphosphate; that is, the anticorrosive filler in Comparative Example 3 is: 15 parts of aluminum tripolyphosphate.
[0132] Comparative Example 4: The 200 low molecular weight polyamide in Example 1 was replaced with an equal amount of EPIKURE 3115-X-70A, the solid content of EPIKURE 3115-X-70A was 70%, and the amine value was 161-173 mg KOH / g.
[0133] The present invention adopts relevant standards to carry out various performance tests on the epoxy primer samples of various embodiments and comparative examples. The results are shown in Table 1.
[0134] .
[0135] It can be seen from the test results that the performance indicators of all embodiments are significantly better than those of the comparative examples, indicating that the epoxy primer of the present invention can meet the needs of complex usage environments and can still have high performance in complex environments.
[0136] The comparative examples of the present invention are all based on Example 1, with targeted changes made in the ingredients. It can be verified from the test results that:
[0137] Compare the adhesion, bending, impact resistance, thermal shock and other test results of Example 1 and Comparative Example 1. It can be seen that compared with the formula of Comparative Example 1, the present invention adopts a compounding method of aliphatic flexible epoxy resin and bisphenol A epoxy resin to introduce aliphatic chains, which significantly improves the flexibility, adhesion and impact resistance of the primer.
[0138] In addition, both Comparative Examples 2 and 3 have aliphatic flexible epoxy resins; therefore, by comparing the test results of salt water resistance, salt spray resistance and thermal shock tests of Comparative Example 1 and Comparative Examples 2 and 3, it can also be proved that the aliphatic flexible epoxy resin of the present invention also effectively improves the corrosion resistance and thermal shock resistance of the primer.
[0139] By comparing the test results of the cross-hatch test, two-year long-term detection, salt water resistance, salt spray resistance, etc. of Example 1 and Comparative Example 2, it can be seen that the wear-resistant filler compounded with precipitated barium sulfate and polyurethane microspheres of the present invention can effectively improve the wear resistance, corrosion resistance and other properties of the primer film.
[0140] The test results of the cross-hatch test, two-year long-term test, salt water resistance, salt spray resistance, etc. of Example 1 and Comparative Example 3 are compared. It can be seen that the present invention adopts calcium-based bentonite, and the anti-corrosion filler composed of the aluminum tripolyphosphate and calcium-based bentonite can effectively improve the corrosion resistance and adhesion of the primer film.
[0141] By comparing the drying time test results of Example 1 and Comparative Example 4, it can be seen that the use of 200 low molecular weight polyamide as a curing agent in the present invention can effectively shorten the curing time.
[0142] In addition, compared with Comparative Examples 2 and 4, the formula of Comparative Example 3 contains polyurethane microspheres and 200 low molecular weight polyamide. Therefore, the test results of the drying time of Comparative Example 3 are compared with those of Comparative Examples 2 and 4. It can be proved that the polyurethane microspheres can react with 200 low molecular weight polyamide to shorten the curing time.
[0143] In addition, the composition of the wear-resistant filler and the anti-corrosion filler of Comparative Example 1 is the same as that of Example 1. Therefore, by comparing the anti-sagging test results of Comparative Example 1 with those of Comparative Examples 2-4, it can also be proved that the composition of the wear-resistant filler and the anti-corrosion filler of the present invention effectively improves the sagging performance of the primer and has good workability.
[0144] In summary, the present invention provides an epoxy primer, which increases the adhesion and impact resistance of the epoxy resin after curing by compounding aliphatic flexible epoxy resin with bisphenol A epoxy resin, and improves the cold and hot shock resistance of the paint film. It avoids the problems of cracking and peeling caused by vibration when the primer is applied to the energy storage box. The present invention also provides a preparation method of the epoxy primer.
[0145] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. An epoxy primer, characterized in that: It comprises component A and component B, wherein the mass ratio of component A to component B is 5-7:1; Calculated by weight, the component A consists of 15 to 35 parts of bisphenol A epoxy resin, 1 to 5 parts of aliphatic flexible epoxy resin, 0.5 to 5 parts of rheology control additive, 5 to 14 parts of cosolvent, 0.4 to 1 part of wetting dispersant, 0.1 to 0.6 parts of defoamer, 10 to 20 parts of pigment, 10 to 30 parts of wear-resistant filler, 5 to 15 parts of anticorrosive filler, and 0.4 to 1 part of leveling agent; The epoxy equivalent of the bisphenol A epoxy resin is 450-500 g / mol; the aliphatic flexible epoxy resin is polyglycol diglycidyl ether resin, the epoxy equivalent is 310-330 g / mol, the solid content is ≥99%, and the viscosity is 50-80 mPa·s; the wear-resistant filler is a compound of precipitated barium sulfate and polyurethane microspheres; the weight parts of the precipitated barium sulfate and the polyurethane microspheres are both 5-25 parts, and the sum of the weight parts of the two is 10-30 parts; Calculated by weight, the B component consists of 40-70 parts of a polyamide curing agent, 1-5 parts of an epoxy drier, and 15-30 parts of a cosolvent; Among them, the polyamide curing agent is 200 low molecular weight polyamide, with a solid content of ≥99% and an amine value of 230~260mgKOH / g; the anti-corrosion filler is a compound of aluminum tripolyphosphate and calcium-based bentonite, the weight parts of both are 2~10 parts, and the sum of the weight parts of the two is 5~15 parts.
2. The epoxy primer according to claim 1, characterized in that The polyurethane microspheres have a solid content of ≥99%, an oil absorption of 70-120%, and a particle size of <50µm.
3. The epoxy primer according to claim 1, characterized in that The polyurethane microspheres are Acure D820.
4. The epoxy primer according to claim 1, characterized in that The epoxy drying agent is: 2,4,6-tris(dimethylaminomethyl)phenol.
5. The epoxy primer according to claim 1, characterized in that The defoamer is: a polymer defoamer that does not contain silicone; The wetting and dispersing agent is: a modified polyurethane polymer; The rheology control additive is: a polyamide wax expansion particle dispersion with 20% effective ingredients; The leveling agent is: an acrylic polymer surface control agent having 50% non-volatile matter; The pigment is: titanium dioxide, phthalocyanine blue, carbon black, iron oxide red or iron oxide yellow; The co-solvent is: xylene, methyl ethyl ketone, n-butanol or isopropanol.
6. A method for preparing an epoxy primer as claimed in any one of claims 1 to 5, characterized in that: include: The preparation of component A comprises the following steps: S1: adding the bisphenol A epoxy resin, aliphatic flexible epoxy resin and rheology control agent into a mixing tank according to predetermined weight portions; stirring for 10-30 minutes, and controlling the fineness to be ≤20 µm; The stirring speed is: 2000~3000r / min, and the temperature in the batching tank is: 40-60℃; S2: adding a cosolvent, a wetting and dispersing agent, a defoaming agent, a pigment, a wear-resistant filler, an anticorrosive filler, and a leveling agent according to predetermined weight portions, and stirring to obtain a mixed solution; Stirring speed: 1000~1500 r / min; S3: transferring the mixed liquid to a grinding tank and grinding it to a predetermined fineness; The temperature in the grinding jar is: 20~40℃; S4: reducing the stirring speed to 1000 r / min, adding a co-solvent, stirring evenly, and filtering through a 100-mesh filter to obtain the A component; Preparation of the B component: Adding a cosolvent, a polyamide curing agent, and an epoxy drier into a batching tank according to predetermined weight portions; stirring evenly, and filtering through a 120-mesh filter to obtain the B component; The stirring speed is: 500~1500r / min, and the stirring time is: 40-60min.
Citation Information
Patent Citations
Solvent type double-composition epoxy coating material quick to solidify at low temperature and preparation method thereof
CN103409037A
Water-based wear-resistant antibacterial floor decorative coating and preparation method thereof
CN117447906A